First observation of the decays B̄(s)0→Ds+K -π+π- and B̄s0→D s1(2536)+π- - Aaij, R; Abellan Beteta, C; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; et al. (2012)
The first observation of the decays B̄s0→Ds+K -π+π- and B̄0→ Ds+K-π+π- are reported using an integrated luminosity of 1.0 fb-1 recorded by the LHCb experiment. The branching fractions, normalized with respect to B̄s0→Ds+π -π+π- and B̄s0→Ds+K -π+π-, respectively, are measured to be B(B̄s0→Ds+K-π+π-) B(B̄s0→Ds+π-π+π-)=(5. 2±0.5±0.3)×10-2 and B(B̄0→ Ds+K-π+π-)B(B̄s0→Ds+K -π+π-)=0.54±0.07±0.07, where the first uncertainty is statistical and the second is systematic. The B̄s0→Ds+K-π+π- decay is of particular interest as it can be used to measure the weak phase γ. First observation of the B̄s0→Ds1(2536)+π -, Ds1+→Ds+π-π+ decay is also presented, and its branching fraction relative to B̄s0→Ds+π -π+π- is found to be B(B̄s0→ Ds1(2536)+π-,Ds1+→Ds+π -π+)B(B̄s0→Ds+π -π+π-)=(4.0±1.0±0.4) ×10-3. © 2012 CERN.